2021
DOI: 10.1186/s12884-021-03611-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceived differences on the role of traditional birth attendants in rural Tanzania: a qualitative study

Abstract: Background In many low to middle income countries, traditional birth attendants (TBAs) play various roles (e.g., provision of health education, referral to hospitals, and delivery support) that can potentially improve women’s access to healthcare. In Tanzania, however, the formal healthcare systems have not acknowleded the role of the TBAs. TBAs’ contributions are limited and are not well described in policy documents. This study aimed to examine the perspectives of both TBAs and skilled birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…TBAs are the first point of call in most rural communities for any maternal and child healthcare. [ 22 ] It is not surprising that most studies in African countries continue to show higher utilization rates. Two different studies in Ethiopia[ 23 , 24 ] observed TBA utilization rates of 51.4% and 47.0%, respectively, which were more than what was observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…TBAs are the first point of call in most rural communities for any maternal and child healthcare. [ 22 ] It is not surprising that most studies in African countries continue to show higher utilization rates. Two different studies in Ethiopia[ 23 , 24 ] observed TBA utilization rates of 51.4% and 47.0%, respectively, which were more than what was observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, differences between extreme poverty in large regions like Dar es Salaam and rural areas manifest inequality differently (intersectionally). For example, neonatal mortality in large, urbanized regions may be exacerbated by a lack of traditional midwives who assist rural women in the hinterlands when giving birth (Shimpuku et al 2021). Traditional birth attendants have been shown to significantly lower stillbirths, neonatal, and perinatal mortality (Shimpuku et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected in all 41 primary and 13 secondary schools in three wards of Korogwe District, an area in Northeast Tanzania [14]. These three wards were selected from rural, urban, and middle, respectively to make a representative population in Korogwe District.…”
Section: The Study Settingmentioning
confidence: 99%